Advancements in the application and research of baculovirus vector vaccines for respiratory diseases in human - Yuan, Jinghua; Chen, Jingyu; Zhao, Qingzhi; Xu, Jialu; Li, Xianwei; Zhang, Yijie; Li, Hairun; Chen, Xintong; Zhao, Ling; Zhang, Xiaofen; Li, Hongyu; Chen, Keda (Frontiers in Microbiology, 2025)
The rapid spread of respiratory diseases, such as influenza, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), Middle East Respiratory Syndrome Coronavirus (MERS-CoV), and Respiratory Syncytial Virus (RSV), poses significant challenges to global public health systems. Vaccination remains the most effective strategy to mitigate these threats. Baculovirus Expression Vector Systems (BEVS) have emerged as a promising platform for vaccine development, addressing key limitations of traditional methods, including complex production processes, lengthy timelines, and high costs. BEVS offers distinct advantages, such as enhanced efficacy, safety, cost-effectiveness, and scalability for large-scale manufacturing. This review highlights the application of BEVS in combating respiratory diseases by analyzing preclinical studies, clinical trials, and approved vaccines targeting these pathogens. It also examines recent advancements in BEVS technology, emphasizing its capacity to accelerate vaccine development and respond to emerging respiratory threats. By focusing on the synergy between BEVS and respiratory disease prevention, this review provides valuable insights to guide global vaccine innovation.